Double Q-switch Ho:Sc2SiO5 laser by acousto-optic modulator combined with Cr2+:ZnSe saturable absorber. (1st January 2018) - Yang, Xiao-tao; Zhang, Peng; Xie, Wen-qiang; Li, Lin-jun
Highlights: Q-switch Ho:Sc2 SiO5 laser modulated by a acousto-optic modulator and a Cr 2+ :ZnSe is reported for the first time. The maximum peak power is obviously higher than the actively and passively Q-switch ones. Ho:Sc2 SiO5 possesses large energy splitting, wide absorption and emission spectrum. Abstract: A double Q-switch (DQS) Ho:Sc2 SiO5 laser modulated by a acousto-optic modulators (AOM) combined with a Cr 2+ :ZnSe saturable absorber (SA) was reported for the first time. The actively Q-switch (AQS) and passively Q-switch (PQS) were also studied. For the DQS mode, a maximum average output power of 2.49 W under the incident pump power of 12.5 W was obtained, corresponding to a slope efficiency of 24%. The characteristics of the DQS Ho:SSO laser versus different repetition frequencies (RF) of the AOM were researched. The maximum single-pulse energy of the DQS Ho:SSO laser was calculated to 1.98 mJ. The maximum peak power of the DQS Ho:SSO laser was 49.5 kW. The output beam quality factor M 2 of DQS Ho:SSO laser was measured to be 1.15 with the highest peak power by knife-edge method at different positions.